2017
DOI: 10.1159/000477177
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy, Inner Limiting Membrane Peel, and Gas Tamponade in the Management of Traumatic Paediatric Macular Holes: A Case Series of 13 Patients

Abstract: Purpose: To review the outcomes of pars plana vitrectomy, internal limiting membrane (ILM) peel, and gas tamponade in the management of traumatic paediatric macular holes. Methods: Retrospective case series of children undergoing vitrectomy, ILM peel, and gas tamponade for traumatic macular hole between March 2007 and July 2014. Main outcome measures were postoperative visual acuity at 3 and 12 months, anatomic closure rate, and surgical complications. Results: Anatomic macular hole closure was achieved in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…The IOP scores at the beginning and end of the follow-up period were not significantly different. The findings from the present study are supported by several studies that have shown that endotamponade with silicone oil predisposed patients undergoing PPV to developing secondary glaucoma [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
“…The IOP scores at the beginning and end of the follow-up period were not significantly different. The findings from the present study are supported by several studies that have shown that endotamponade with silicone oil predisposed patients undergoing PPV to developing secondary glaucoma [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, data have been accumulated to support the role of vitrectomy with ILM peeling and intraocular gas tamponade for the treatment of TMH [5,12,13,20,21]. The surgery provides satisfactory anatomic outcomes for most patients, but the functional outcomes vary widely [4].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 12 studies with a total of 117 pediatric patients with a mean age of 12 years who received vitrectomy for the treatment of TMHs 5,31,36,[38][39][40][41][42][43][44][45] (Table 2). Anatomic closure rates after the first surgery ranged from 77% to 100% with a mean overall closure rate of 88%.…”
Section: Vitrectomymentioning
confidence: 99%